The acute toxicity of water hemlock (Cicuta douglasii) in a goat model. (March 2020) - Welch, K.D.; Stonecipher, C.A.; Lee, S.T.; Cook, D.
Abstract: Water hemlock ( Cicuta douglasii ) is one of the most toxic plants to livestock and humans. Little is known regarding the amount of plant required to cause death. The objective of this study was to determine a lethal dose of water hemlock in a goat model. Plants were dosed to goats via oral gavage of freeze-dried ground plant material. The results from this study suggest that 1–2 fresh tubers would be lethal to goats. Highlights: Tubers are the most toxic part of the water hemlock plant. A dose of 0.25 g/kg BW of dried water hemlock tubers can be lethal to goats. A dose of 0.1 g/kg BW of dried water hemlock tubers is not toxic to goats. A dose of 10 g/kg BW of dried water hemlock above ground parts can be toxic to goats. Water hemlock toxins can be identified in rumen contents from poisoned goats.